Interpretação do patrimônio geológico do Parque Nacional da Chapada dos Veadeiros aplicada ao turismo - Barbosa, Gabriela Couto (2017)
Despite being considered a recent subject, geodiversity has been gaining more and more space mainly within the academy. Discussions revolve mainly on the importance of conservation and geodiversity preservation, which is as important to tell the Earth's history as biodiversity and can be as susceptible as. Tourism activity has been appropriating geodiversity for some time. It is normal the practice of tourism in natural environments. Such activities do not always provide care for the conservation of geodiversity elements. In this context, geodiversity introduces three important concepts for understanding the importance of conservation and preservation: geological patrimony, geoconservation and geotourism. Geological heritage, as the name itself already presents, shows specific values, which differentiate the geodiversity elements. The Chapada dos Veadeiros National Park, located in the northern portion of the Goiás State, presents peculiar geology and geomorphology. This peculiarity is responsible for the formation of tourist attractions that attract visitors from all over Brazil. However, most visitors are attracted only by the scenic beauty of the place. The present work aims to interpret the geological heritage of the National Park of Chapada dos Veadeiros to awake the feeling of geoconservation in the visitors. This work is justified by the fact that the park does not have tools that allow the visitors to know better about the geological formations and the processes that formed them, developing a proximity to the place. The production and application of an interpretative panel was a very enriching experience for both the research and the visitors, which shows the importance of the development of tools of this type.